KETEGUHAN REKAT RESORSINOL FORMALDEHIDA PADA KAYU YANG DIA WETKAN DENGAN CELCURE - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1995)
Production  of laminated  structural  timbers   suitable  for use under severe  conditions  dates back to the development   of resorcinol and phenol-resorcinol   adhesives.    These adhesives  could provide  highly  durable  bonds  with  untreated    wood.     Because  preservative  treatment  of the - wood is commonly  required,   it  became necessary   to  investigate  the effect of the treatment on glue bond strength.This  study  examined  the  shear  strength   of resorcinol formaldehyde on the untreated  and cetcure  treated   timbers.    Additionally,   a mechanical and a chemical surface  activation treat- ments   were   imposed  lo  the  system  prior  lo  gluing.    Species   included for  the  study  were: jeungjing   (Paraserianthes    falcataria   (L.)  Nielsen,   adinandra  (Adinandra brasii  Kobuski) and pala burung (Horsfieldia sylvestris Warrb.).  Defect-free airdried wood slicks measuring  50 mm (radial) x 50 mm (tangential) x 500 mm (longitudinal)  were divided into  two groups,   of which one  group   was celcure-treated    using  an  empty-cell process  and  the  other  was remained  as control.  Each  slick   was  then    cut  into  billets  for  adhesive   lamination.    Surface  activation treatments   were made mechanically by sanding  wood surface with an 80-grit  abrasive  paper, or chemically by smearing wood surface with  IM solution of NaOH approximately 24 h before  gluing.  Resorcinol formaldehyde  was applied  to each surface  at a spread rate of  120  mg/cm2.  Panels  were clamped  at  12   kg/cm2  for  7 h as recommended  by the   adhesive  manufacturer. Each panel  was  cut   into four  shear   specimens,    of  which  two specimens  were  tested   in dry condition   and the remaining  after  24 h immersion  in water at room temperature.    Strength  loss  due to wetting was also determined.Results  showed  that bond strength  of resorcinol formaldehyde varied according  to wood species.    Jeungjing had a weaker bond strength  than adinandra and pala burung.   Preservative treatment  had  no  deteriorating  effects on dry  shear  strength,   but it did  reduce  the wet  shear strength  of  wood laminates. The  application  of surface activation treatments  was more effective on the higher extractive  contained species   (adinandra  and pala  burung) and the  unpreserved laminates.    Surface mechanical  treatment  showed a better improvement on bond strength  than the chemical   treatment.  Jeungjing   experienced  a higher strength  loss during  immersion  than